Avaliação da produção de água (vazão), em função de alterações de uso do solo e da implantação de florestas de eucalipto em larga escala na bacia do Rio Pará- Alto São Francisco/MG - Evandro Luis Rodrigues (2013)
The vegetation plays a fundamental role in maintaining balance and hydrological cycle, with significant functions in controlling the production of water with the permanence of instream flows. However, there is a perception that forest plantations lead to overconsumption of water, remaining many doubts about the actual impact of forests in basins water flow. Thus, the use of mathematical models is an alternative to represent the systems, processes and assist in the understanding of phenomena involving the variables of the water cycle to anticipate and predict potential impacts of changes in land use. In this context, we used the hydrological model SWAT (Soil and Water Assessment Tool) to analyze the dynamics of flow and water production in the Pará river - upper São Francisco river, Minas Gerais, affected by large-scale forestation. We simulated four scenarios of land use and cover as following: current use, original vegetation and reforestation on soil units of Latosol and Argisol. Results indicate a close influence of the vegetation cover in the control of water flow in the basin depending on the physical characteristics and local climate. In comparison with the current use, the scenario of original vegetation cover showed a lower hydro output in 50.63 mm.ano1 corresponding to a 9.43% increase in water consumption for this type of coverage. The reforestation scenarios in areas of soil and in argisoil showed higher water demands with an reduced of 97.62 and 133.31 mm.ano1, in availability. This increase in consumption as 18.19% and 24.84% respectively in each of these scenarios. The results obtained by the SWAT model were satisfactory generating reliable and significant estimates to the analysis. Thus, the results indicate that short and medium term changes in the land and use cover inside a watershed can cause larger or smaller impacts depending on the physical and climatic variables of the water regime.